Kecerdasan Spritual dan Emosional dalam Pendidikan Tahfizd Al-Qur’an - Nor Rochmatul Wachidah; M. Luqmanul Hakim Habibie (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
In Tahfiz Al-Qur’an education, education should have a very complex concept and require a variety of approaches, techniques and the required intelligence. Through a theoretical approach with a qualitative descriptive analytical method with the concept of library research. The author tries to examine books, journals, to get information related to the issues discussed, especially to describe the theoretical studies that have been determined.The result is that the memorizers of AlAl-Qur’an who have practiced Akhlaqul Karimah are aware that they are able to face all kinds of problems that exist very easily. This is because the level of spiritual and emotional intelligence has exceeded the standard of ordinary humans (non-memorizers of Al-Qur’an). This is one part of the miracle of the Qur'an that the long process of memorizing Al-Al-Qur’an is able to make the memorizer have intelligence and a strong memory if in the science of hadith it is referred to as dha> bit and tsiqah. In the end, spiritual and emotional intelligence in the education of Tahfiz al-AlQur’an is a unity that needs each other and is very closely related, and even has a high significance.